The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1590/s0100-736x2017000200004
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre adiposidade, perfil energético, proteínas inflamatórias e lesões osteoarticulares em equinos jovens sobre diferentes sistemas de criação

Abstract: High carbohydrate diets are increasingly used in horse rearing systems. This can result in weight gain and fat accumulation in young horses. There is a growing incidence of juvenile osteoarthritis and other inflammatory conditions in overweight young horses that undergo intense physical exercise. The aim of this study was to associate corporal adiposity with energy profile, serum concentration of acute phase proteins and presence of osteo-articular lesion in the tarsal region of young horses raised in two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This slight hypertriglyceridemia in foals may be a manifestation of hepatic immaturity at birth (Schmid and McDonagh 1978), or simply a result of the milk consumption, as TRIG are the most abundant lipids in milk (Beitz 1996). Amaral et al (2017) measured the adiposity between foals created during extensive and intensive regimens, and observed that the foals of the extensive system showed greater lipid mobilization, characterized by higher levels of TRIG and AGL, similar to findings of this study. Foals 10,46 ± 0,51 10,73 ± 0,22 11,23 ± 0,33 9,55 ± 1,35 11,25 ± 0,23 9,35 ± 0,61…”
Section: Discussionsupporting
confidence: 85%
“…This slight hypertriglyceridemia in foals may be a manifestation of hepatic immaturity at birth (Schmid and McDonagh 1978), or simply a result of the milk consumption, as TRIG are the most abundant lipids in milk (Beitz 1996). Amaral et al (2017) measured the adiposity between foals created during extensive and intensive regimens, and observed that the foals of the extensive system showed greater lipid mobilization, characterized by higher levels of TRIG and AGL, similar to findings of this study. Foals 10,46 ± 0,51 10,73 ± 0,22 11,23 ± 0,33 9,55 ± 1,35 11,25 ± 0,23 9,35 ± 0,61…”
Section: Discussionsupporting
confidence: 85%
“…Since it is understood that IGF-1 is involved in the cartilage repair in osteoarthritic horses, it is believed that the lower levels of IGF-1 are related with non-healing of the articular lesions during the puberty period (around 7-8 months of the foals) [15,17]. In two previous researches with Crioulo horses, it was observed that the foals aged less than 26 months had a 79.2% [18] and 100% [5], of prevalence of articular tarsus lesions. These suggests that the tarsus lesions observed in 92.85% of the 6-month-old foals in the present study could not heal and that lesions should remain in the foals to adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify possible articular changes at the distal tarsal joints, radiographic imaging of the both pelvic members were obtained; and to identify possible distal metacarpal physeal changes, radiographic imaging of the metacarpal-phalangeal joints of both thoracic members was obtained. For each joint, four standard radiographic projections were performed with the RX machine (DR RX EcoRay) 5 [10]: lateromedial, dorsoplantar, dorsolateral -plantaromedial oblique and dorsomedial -plantarolateral oblique. Score grade lesions were classified [33], and are described in Table 1.…”
Section: Foal Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rising prominence of the Crioulo breed and the goal of functional and morphological improvement, a shift in the management of these animals has been observed. There has been a move towards more intensive breeding and adoption of hypercaloric diets rich in complex carbohydrates, leading to various consequences such as obesity, dental problems, orthopedic conditions, and colic (Frank, 2011;Amaral et al, 2017).…”
Section: Introductionmentioning
confidence: 99%